The Effect of Hayes' Strategy on Developing Creative Writing Among Fifth-Grade Literary Students (Journal of the College of Basic Education, 2025)
This research aims to identify "The effect of Hayes' strategy on developing creative writing among fifth-grade literary students."To achieve the research objective, the researcher adopted an experimental method with partial control for two randomly selected groups suitable for the current research conditions. The researcher formulated two null hypotheses.The research sample consisted of (64) female students from the fifth-grade literary level at (Al-Shaheed Naeem Al-Nafakh Preparatory School) in Najaf Governorate, who were randomly selected. The researcher equated the two groups in the following variables: chronological age of students calculated in months, parents' educational attainment, scores on the mental ability test (Henmon-Nelson), and creative writing test.The researcher derived (104) behavioral objectives from the topics specified in the Arabic language book (Reading), and prepared lesson plans that were presented to a group of arbitrators in Arabic language and literature and its teaching methods to verify their validity.The researcher prepared a pre-test and post-test for creative writing skills.The researcher herself taught the students of the two research groups, the experimental group according to Hayes' strategy, and the control group using the traditional method. The experiment lasted for one academic semester, which is the second semester of the academic year (2023/2024(.The researcher statistically analyzed the study data using one-way analysis of variance, chi-square (χ2), Pearson correlation coefficient, Scheffe's method, difficulty coefficient of essay and objective items, discrimination coefficient of essay and objective items, point-biserial correlation coefficient, t-test equation for the significance of the correlation coefficient, interclass correlation coefficient equation, Kruskal-Wallis test, and variance homogeneity test